2020
DOI: 10.3390/su12041671
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Distribution Patterns of Phragmites australis Populations Across an Environmental Gradient in the Salt Marsh Wetland of Dunhuang, China

Abstract: The spatial distribution pattern of plants often reflects their ecological adaptation strategy and is formed by their long-term interaction with environmental factors. In this paper, the clonal plant, Phragmites australis, was investigated across environmental gradients, including the wet zone, the transitional zone and the desert zone of the salt marsh wetland of Dunhuang, China. The characteristics and influencing factors of their fine-scale spatial distribution patterns were studied by point pattern analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Appropriate salt supplementation can increase fiber content and biomass, making it healthier and more robust ( Guan et al., 2017 ). Soil salinity plays a dominant role in determining the growth of P. australis , and high salinity limits the population’s survival ( Schenck et al., 2018 ; Jiao et al., 2020 ; Zhang et al., 2021b ; Barbafieri et al., 2023 ). The results showed that the variation coefficients of plant height at low tidal flat and biomass at high tidal flat of P. australis were 37.06% and 44.6%, respectively, indicating that these two morphological traits were largely affected by environmental factors ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate salt supplementation can increase fiber content and biomass, making it healthier and more robust ( Guan et al., 2017 ). Soil salinity plays a dominant role in determining the growth of P. australis , and high salinity limits the population’s survival ( Schenck et al., 2018 ; Jiao et al., 2020 ; Zhang et al., 2021b ; Barbafieri et al., 2023 ). The results showed that the variation coefficients of plant height at low tidal flat and biomass at high tidal flat of P. australis were 37.06% and 44.6%, respectively, indicating that these two morphological traits were largely affected by environmental factors ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil water content, pH and salinity all affected the spatial distribution intensity of P. australis . Specifically, the spatial distribution pattern intensity was positively correlated with density, height, biomass and stem diameter ( P < 0.01) ( Jiao et al., 2020 ). Soil salinity plays a leading role in the stoichiometric characteristics of carbon, nitrogen, and phosphorus in P. australis leaves and roots ( Zhang et al., 2021b ), which indicates that soil salinity also indirectly influences the stoichiometric characteristics of soil carbon, nitrogen, and phosphorus in P. australis habitat.…”
Section: Discussionmentioning
confidence: 99%
“…recent studies have demonstrated that some clonal plants may be suitable for repairing and restoring vulnerable habitats. These include (a) clonal plants in karst landform habitats, such as Ficus tikoua [20], Alchornea trewioides [21], and Drepanostachyum luodianense [22]; (b) clonal plants in deserts, such as Calamagrostis epigejos [23], Hedysarum leave [24], Hippophae rhamnoides L., Psammochloa villosa [25], and Stenocereus eruca (Cactaceae) [26]; (c) clonal plants in grasslands, such as Leymus chinensis [27,28], Zoysia japonica Steud [29,30], and Buchloe dactyloides [31]; (d) clonal plants in wetlands, such as Phragmites australis [32,33], Paspalum paspaloides [34], Acorus calamus L., and Spartina alterniflora Loisel [34]. Researchers have also been keen to study the invasion mechanism in invasive clonal plants such as Alternanthera philoxeroides [35], Solidago canadensis L. [36], Carpobrotus edulis [37], and Mikania micrantha H.B.K.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some potential limitations are gradually emerging in the sustainable restoration efficiency [6]. Plant populations present different spatial patterns at different spatial scales under the influence of these biological interactions and ecological processes [7]. Therefore, the potential biological interactions and ecological process within saltcedar populations can be explored through spatial pattern analysis, which will provide theoretical guidance for saltcedar restoration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%